TGFBI mutation screening and genotype-phenotype correlation in north Indian patients with corneal dystrophies - Paliwal, Preeti (Molecular Vision, 2010)
PURPOSE: To screen a cohort of corneal dystrophy patients from North India for mutations in the transforming growth factor beta induced (TGFBI) gene, to correlate genotypes to phenotypes, to describe structural implications of various mutations on protein function, and to discuss the implications for diagnosis. METHODS: Eighty affected individuals from 61 unrelated families, who were diagnosed with autosomal dominant granular and/or lattice corneal dystrophy, were recruited for the study. Detailed clinical evaluation was undertaken for these patients to establish their corneal phenotypes. Genomic DNA was isolated from peripheral blood samples and all exons of TGFBI were screened for mutations by polymerase chain reaction (PCR) and direct DNA sequencing. Protein molecular dynamics (MD) simulations were performed for the mutations detected to assess the changes in protein structure. RESULTS: The most common mutations seen were Arg555Trp and Arg124Cys. Two novel mutations, Ser516Arg (c.DNA1548C>G), with a phenotype similar to granular corneal dystrophy I (GCDI), and Leu559Val (c.DNA1675T>G), with an atypical phenotype closely resembling epithelial basement membrane dystrophy/map dot fingerprint dystrophy, were identified. Protein modeling studies involving wild type and mutant protein indicated that the Leu559Val is a destabilizing mutation and that Ser516Arg could adversely affect the specific binding of Fas1 domain 4 with other proteins. In addition, two single-nucleotide polymorphisms, rs4669 and rs11331170, were also identified. Mutations were not identified in 8 affected individuals, 6 of whom were diagnosed with bowman layer dystrophy and 2 with lattice corneal dystrophy. CONCLUSIONS: This is the first comprehensive report of TGFBI mutations covering a large part of North India. Identification of novel mutations, the presence of phenotypic variability, and the genetic heterogeneity seen in our cases stress the need for mandatory screening of TGFBI for precise diagnosis and classification of corneal dystrophies.